ANALISIS LEVEL BELANJA PEMERINTAH DAERAH KABUPATEN KONAWE SELATAN TAHUN 2011-2020 - Syamsul Alam (Journal Publicuho, 2022)
This study aims to analyze the level of local government spending in South Konawe Regency in 2011-2020 from the perspective of the golden rule. The research method used is existing statistics research of a non-reactive method. The data used is numerical data for the time series of local government spending and gross regional domestic product 2011-2020. The quantitative data analysis technique used is the percentage statistic in SPSS Forecasting version 23.0. The results showed that the level of local government spending in South Konawe Regency in 2011-2020 was not optimal because it was far below the minimum criteria recommended as the golden rule in the theoretical literature on government spending. This sub-optimal level of local government spending has the connotation of the local government's inability to respond to increasing public demands and expectations, at least in providing public goods that the market cannot afford. The local government of South Konawe Regency, if it wants to be of higher quality, needs to increase its level of spending to an optimal level